Impediments to river rehabilitation - Nuruzzaman, Md.; Mamun, Abdullah Al; Salleh, Md. Noor (John Wiley and Sons Inc, 2016)
Rehabilitation of river ecosystems is generally initiated when a river is no longer able to provide benefits to humans and other living beings. The major purposes of river rehabilitation projects are improving water quality, conserving nature, rehabilitating fisheries and riparian habitats, flood mitigation, and creating recreational opportunities.For a river rehabilitation project to be successful,it must have specific and clearly explained objectives, although these objectives will vary for each project depending upon factors such as economics, public demand,ecosystem benefits, and the like. In this article, we provide a critical analysis of the purposes that drive river rehabilitation projects and we identify and discuss impediments that can cause a project to deviate from its intended goals. We also discuss major constraints on rehabilitation efforts that can result in failed projects.